2020
DOI: 10.1101/2020.05.06.080606
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multiple early introductions of SARS-CoV-2 into a global travel hub in the Middle East

Abstract: International travel played a significant role in the early global spread of SARS-CoV-2. Understanding transmission patterns from different regions of the world will further inform global dynamics of the pandemic. Using data from Dubai in the United Arab Emirates (UAE), a major international travel hub in the Middle East, we establish SARS-CoV-2 full genome sequences from the index and early COVID-19 patients in the UAE. The genome sequences are analyzed in the context of virus introductions, chain of transmis… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 10 publications
0
20
0
Order By: Relevance
“…This study was approved by the Total RNA Library kit from Illumina (San Diego, CA, USA) as previously described. 12,13,14 Libraries were then sequenced using the NovaSeq SP Reagent kit (2 X 150 cycles) from Illumina (San Diego, CA, USA) to generate a minimum of 15M reads per sample (Supplementary Table 1).…”
Section: Patient Cohort and Ethics Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was approved by the Total RNA Library kit from Illumina (San Diego, CA, USA) as previously described. 12,13,14 Libraries were then sequenced using the NovaSeq SP Reagent kit (2 X 150 cycles) from Illumina (San Diego, CA, USA) to generate a minimum of 15M reads per sample (Supplementary Table 1).…”
Section: Patient Cohort and Ethics Statementmentioning
confidence: 99%
“…described 12. Briefly, mild cases were asymptomatic or had mild non-life-threatening symptoms, while moderate cases presented with symptoms (such as persistent fever) requiring medical attention and/or hospitalization.…”
mentioning
confidence: 99%
“…The COVID-19 pandemic has rapidly spread around the globe during the first six months of 2020. The causative coronavirus, SARS-CoV-2, is the subject of many studies using genomic analysis providing key insights into viral diversity across cities 1 , provinces 2-5 , countries 6-11 , and globally 12 . SARS-CoV-2 has an estimated mutation rate of 0.71-1.40×10 −3 13 , which translates to 21-42 mutations per year.…”
Section: Introductionmentioning
confidence: 99%
“…Genome-based studies of the SARS-CoV-2 variants in different geographical regions identified multiple introductions associated with international travel routes (for example, (Bugembe et al 2020, Tayoun et al 2020, Worobey et al 2020). The introductions to the UK (>1400 events) have been recorded to early February and throughout that month (20% of transmission lineages) with the majority (80%) being established in March (Plessis et al 2020).…”
Section: Introductionmentioning
confidence: 99%